WAYS TO PROTECT CREDITORS’ RIGHTS DURING BANKRUPTCY PROCEEDINGS - Фокін, Кирило Юрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
The purpose of this article is to analyze legal regulation, scientific and expert basis in the field of methods with protection of creditors’ rights in Ukraine. The methodological basis of the research comprise general scientific methods of scientific knowledge, such as integrated and interdisciplinary. Results: the main ways of creditors’ rights protection in Ukraine are defined and ways of improvement of legislation in this sphere are suggested. Discussion: the basis of national legislation in the sphere of creditors’ rights protection. Despite the formal equality of creditor and debtor according to the domestic legislation, in fact the debtor has a wide enough arsenal of tools to avoid liability for improper performance of obligations. Considering that the issue of protection of creditors’ rights is becoming more and more important every year, we try to analyze the most effective ways to protect creditors’ rights, which are now relevant. To date, the protection of the rights and interests of creditors is not limited to entry in the creditor registry and does not end at this stage. Creditors have a significant range of means and opportunities to defend their legitimate interests throughout all procedures that may apply to the debtor, namely: property management, amicable settlement, rehabilitation and liquidation. To a certain extent, these procedures can be considered as ways for creditors to protect their rights and satisfy their claims. In order to understand how they affect certain issues and the extent to which they are available at the stage of a procedure, each of them should be considered separately. We can conclude that the current bankruptcy legislation contains a lot of gaps and shortcomings, despite the fact that from the time of Ukraine’s independence until now it has experienced many changes, new versions and even the adoption of the new code. It would be expedient to expand the list of creditors, provide their definition and clearly differentiate their legal status. Such details would help to better understand the status and place of each creditor. We can conclude that there is a need to expand the liability for arbitrators by law. Its actions can cause harm to creditors both through careless and unprofessional performance of their duties and through abuse of their rights.